The viability of pedestrian street malls as an instrument to revitalise declining central business districts with reference to the St George's Street Mall in Cape Town - Van der Merwe, Lolita (Stellenbosch : Stellenbosch University, 2012)
Study project (M.A.) -- University of Stellenbosch, 1990.